Hubungan Kepemimpinan Kepala Sekolah dengan Disiplin Kerja Guru di Sekolah Dasar Negeri Se Kecamatan Koto XI Tarusan Kabupaten Pesisir Selatan - Saputri, Melati; Nellitawati, Nellitawati (ARZUSIN, 2024)
Based on the phenomenon that emerged in educational institutions indicating that teacher work discipline is still low. This is thought to be influenced by the leadership of the principal. The purpose of this study was to analyze the relationship between principal leadership and teacher work discipline. This type of research is correlational research. Populasi are all teachers in SDN se Kecamatan Koto XI Tarusan with number 471. A large sampel of 44 people who are determinand by cluster random sampling technique. The research instrument was a questionnaire likert scale models that have been tested for validity and reliability. Data were analyzed using product moment correlation technique. The results of the data analysis showed that: leadership in SDN se Kecamatan Koto XI Tarusan are in good categories (3,4) and work discipline teacher in SDN se Kecamatan Koto XI Tarusan in good category (3,5). There is a significant relationship between leadership at work discipline teacher at SDN se Kecamatan Koto XI Tarusan with correlation coefficients at the level of 95% with t count = 2,385 > t table = 1,680. From the result it can be concluded that leadership is one of the factors that influence teacher work discipline.